1997
DOI: 10.1677/joe.0.1530475
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of human neutrophil function in vitro by gastrin

Abstract: We have studied the effects in vitro of gastrin-17 and gastrin-34, at concentrations from 10(-14) M to 10(-6) M, on several of the functions of peripheral blood human neutrophils, i.e. adherence to substrate, mobility (spontaneous and directed by a chemical gradient or chemotaxis), ingestion of inert particles (latex beads) and cells (Candida albicans) and superoxide anion production. Both gastrins inhibited several steps of the phagocytic process of human neutrophils, such as mobility and ingestion. By contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…Whereas gastrin is known to significantly modulate both the proliferation levels of many tumor types (Rehfeld and van Solinge, 1994) and the migration levels of various cell types of the immune system (de la Fuente et al, 1997Fuente et al, , 1998, we were the first to show that gastrin is able to modulate both proliferation (Camby et al, 1996) and migration (De Hauwer et al, 1998) in human tumor astrocytes. These data could relate to the fact that cholecystokinin (CCK) and CCK-related peptides (gastrin) constitute the most abundant peptide system in the brain (Rehfeld and van Solinge, 1994), with gastrin-induced effects mediated through the CCK B receptor.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Whereas gastrin is known to significantly modulate both the proliferation levels of many tumor types (Rehfeld and van Solinge, 1994) and the migration levels of various cell types of the immune system (de la Fuente et al, 1997Fuente et al, , 1998, we were the first to show that gastrin is able to modulate both proliferation (Camby et al, 1996) and migration (De Hauwer et al, 1998) in human tumor astrocytes. These data could relate to the fact that cholecystokinin (CCK) and CCK-related peptides (gastrin) constitute the most abundant peptide system in the brain (Rehfeld and van Solinge, 1994), with gastrin-induced effects mediated through the CCK B receptor.…”
mentioning
confidence: 72%
“…C6 cells were also preincubated in vitro with various concentrations of gastrin before their stereotactic implantation into the rats' brains to study the direct effects of gastrin on in vivo C6 glioma progression. The potential gastrin-induced immunomodulatory counter-effects on C6 gliomas and 9L gliosarcomas stereotactically implanted into the rats' brains were also investigated, because gastrin has a chemotactic influence on a large set of cells of the immune system (de la Fuente et al, 1997Fuente et al, , 1998. It should be emphasized that the C6 model suffers from some limitations because it is allogenic and so induces significant host-mediated immunogenic responses (Parsa et al, 2000).…”
mentioning
confidence: 99%
“…Immune System Measurements Adherence Capacity For adherence capacity measurement, the method described by De la Fuente et al [45] was used. The results were expressed as Adherence Index, which is [(initial cells/ml -effluent cells/ml)/ (initial cells/ml)] !…”
Section: Instrumentsmentioning
confidence: 99%
“…The phagocytosis assay was carried out following the method described by De la Fuente et al [45] . The number of particles ingested by 100 neutrophils is expressed as the phagocytic index, while the number of ingesting neutrophils per 100 neutrophils is expressed as the phagocytic efficiency.…”
Section: Phagocytosismentioning
confidence: 99%
“…We have already shown that gastrin is able to modify not only the cell proliferation level in human glioblastomas (Camby et al, 1994(Camby et al, , 1996, but also their level of migration (DeHauwer et al, 1998). De la Fuente's group has also evidenced the e ect of gastrin on the migration features of various cells of the immune system (De la Fuente et al, 1997Fuente et al, , 1998. Previous studies have shown that peptides related to gastrin family induce actin stress ®bers assembly (Taniguchi et al, 1996).…”
Section: Introductionmentioning
confidence: 96%